Case Report: Oral and fecal microbiota in a super-donor: the healthy microbiota paradigm for fecal transplantation - Ortiz-Olvera, Nayeli; Fernández-Figueroa, Edith A.; Argueta-Donohué, Jesús; Miranda-Ortíz, Haydee; Ruiz-García, Erika (Frontiers in Microbiomes, 2023)
Despite the numerous Fecal Microbiome Transplantation trials implemented, knowledge about the actual composition of a "healthy microbiota" remains scarce. The aim of this research was to describe the differences in the composition of oral and fecal microbiota in a super-donor. The microbiota analysis was done using Next Generation Sequencing of the V3 and V4 regions of the bacterial 16S rRNA gene. The biodiversity found in the mouth was very rich, with 56 species identified, and a predominance of the Veillonella, Haemophilus, and Streptococcus genera. It is worth mentioning the presence (2.33%) of Fusobacterium nucleatum in the mouth. In feces, Bacteroides and Faecalibacterium genera predominated, with the species F. prausnitzii being most abundant. This analysis shows that the diversity of the microbiota of a super donor, the interaction between the different genera and species present, plays a fundamental role for the effectiveness of its product in fecal matter transplantation. This suggests that transplanted gut microorganisms have the ability to maintain or recover health in a dynamic process between the microbiota and the host. Our findings encourage further research which will result in the development of bacterial therapies in infectious and inflammatory diseases.